2004
DOI: 10.1136/jcp.57.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastric precancerous lesions in Ardabil, a high incidence province for gastric adenocarcinoma in the northwest of Iran

Abstract: Background/Aims: Ardabil Province, in northwestern Iran, has the highest rate of gastric (predominantly cardia) adenocarcinoma in Iran. This study aimed to investigate the feasibility of endoscopic screening and to look for associated Helicobacter pylori infection and gastric precancerous lesions. Methods: One thousand one hundred and five adult volunteers, residents of Ardabil and Meshkinshahr, districts, 40 years old and above were selected and invited by a simple random household canvass in rural and urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
7
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 20 publications
4
86
7
1
Order By: Relevance
“…Invasive methods due to ethical issues and UBT because of the use of radioactive materials, are prohibited in pregnancy (35). Invasive methods due to ethical issues and UBT due to the use of radioactive materials are prohibited in pregnancy (35). In most of the studies that investigated the prevalence of H. pylori among pregnant women (80%) based on diagnostic method, serology was the dominant method and this amount was measured to be 49% which had a slight difference with general estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive methods due to ethical issues and UBT because of the use of radioactive materials, are prohibited in pregnancy (35). Invasive methods due to ethical issues and UBT due to the use of radioactive materials are prohibited in pregnancy (35). In most of the studies that investigated the prevalence of H. pylori among pregnant women (80%) based on diagnostic method, serology was the dominant method and this amount was measured to be 49% which had a slight difference with general estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive methods due to ethical issues and UBT because of the use of radioactive materials, are prohibited in pregnancy (35). Invasive methods due to ethical issues and UBT due to the use of radioactive materials are prohibited in pregnancy (35).…”
Section: Discussionmentioning
confidence: 99%
“…and due to late diagnosis, it is mostly diagnosed in the advanced stages of the disease (Eskandar et al, 2006). Gastric cancer incidence has had a slow increase during three past decades in Iran and in 2002 has increased twice in comparison with the three past decades (Malekzadeh et al, 2004;Sadjadi et al, 2006). The incidence trend of gastric and esophagus cancer has decreased dramatically in the Iranian residents of Canada (Sadjadi et al, 2009) which could be an indication for the high impact of lifestyle and environmental factors in the incidence of stomach cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study performed by histopathology in Ardabil, northwest of Iran, revealed about 90% of H. pylori infection in the normal population, older than 40 years old (7). There are several techniques available for detection of H. pylori.…”
Section: Introductionmentioning
confidence: 99%